Improvement of Territorial Management System Modern Methods of Territorial Economy Development - Davronov Kilichbek Firdavs ugli (International Journal on Economics, Finance and Sustainable Development, 2022)
Creating (maintaining) a single market space with the radical transformation of the market, the formation of regional markets and the development of local self-government, indeed the absolute importance of scientific support in the field of regional governance identified the need for a deeper study of issues to improve the effectiveness of management.